1928
DOI: 10.1002/jlac.19284610105
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die Membran der Sporen und Pollen. I. 1. Lycopodium clavatum L

Abstract: Die basische Grnppe ist also relativ schwach. Eine weitere Untersuchnng dieser Stoffe ist im Gange.Da beobachtet worden war, daS das hitzekoagnlierte Phycocrythrin an Alkohol einen violett gefarbten Stoff abgibt, wurde 0,2924 g mit Slethylalkohol verrieben und nach 1 tligigem Stehen durch einen gewogenen Glasfiltertiegel gesogen, mit Alkohol und Ather gewaschen und getrocknet. Dabei war eine Gewichtsabnahme von 0,079 g (2,7 Proc.) Z e t z s c h e und Buggier,9 n h y d r o 8 p o r o n i n. 2 g Sporonin wurden m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 4 publications
0
24
0
Order By: Relevance
“…The numerous publications by Zetzsche and co-workers between 1928 and 1937 were a major progress in deciphering the chemical structure of the remarkably stable spore and pollen walls. They first used "Sporonin" to characterize the resistant compound of Lycopodium spores (Zetzsche and Huggler, 1928). When this team realized that the angiosperm "Pollenin" and the lycopsid "Sporonin" are very similar, they coined the term "Sporopollenin" (Zetzsche and Vicari, 1931) which is still in use today.…”
mentioning
confidence: 99%
“…The numerous publications by Zetzsche and co-workers between 1928 and 1937 were a major progress in deciphering the chemical structure of the remarkably stable spore and pollen walls. They first used "Sporonin" to characterize the resistant compound of Lycopodium spores (Zetzsche and Huggler, 1928). When this team realized that the angiosperm "Pollenin" and the lycopsid "Sporonin" are very similar, they coined the term "Sporopollenin" (Zetzsche and Vicari, 1931) which is still in use today.…”
mentioning
confidence: 99%
“…While the stability and resistance of sporopollenin account for the preservation of ancient pollen grains for millions of years with nearly full retention of morphology (Doyle and Hickey, 1976;Friis et al, 2001), these same qualities make it extremely difficult to study the chemical structure of sporopollenin. Thus, although the first studies on the composition of sporopollenin were reported in 1928 (Zetzsche and Huggler, 1928), the exact structure of sporopollenin remains unresolved. At present, it is thought that sporopollenin is a complex polymer primarily made of a mixture of fatty acids and phenolic compounds (Guilford et al, 1988;Wiermann et al, 2001).…”
mentioning
confidence: 99%
“…These findings are interpreted as meaning that phenylpropane metabolism via phenylalanineammonia lyase is involved in sporopollenin biosynthesis, as highly purified sporopollenin contains no nitrogen (Zetzsche and Huggler 1928;Shaw and Yeadon 1966;S. 'Apeldoorn' was always seen with U-14C-phenylalanine than with other substances.…”
Section: Discussionmentioning
confidence: 89%